Unele aspecte privind realizarea principiului universalităţii dreptului electoral [Articol] - Roșca, Victoria; Romandaș, Nicolae (Academia de Administrație Publică, 2011)
The principle of the universality of the electoral low represents one of the most important principles of the citizens’ participation to the election. But if we examine the historical evolution of the method of election, we detect that there were and are a lot of different limitations of this type of right. Some of them are the propriety qualification, the sex qualification, the religious qualification, the age qualification, the capacity qualification, and etc. All of them were relevant for a definite period of time, or there are qualifications that persist nowadays.